Development of an unmanned airship for magnetic exploration. Issue 4 (4th July 2021) - Kim, Bona; Lee, Seulki; Park, Gyesoon; Cho, Seong-Jun
Abstract : An unmanned airship was used to overcome the limitations of conventional aeromagnetic exploration systems. The airship was fabricated from non-magnetic fibre-reinforced plastic and urethane cloth, and filled with helium. The maximum payload is 10 kg and the flight time (with all equipment installed) is approximately 1 h. The airship is simple to move and store prior to gas injection, and easy to handle in the field because of its small size. An automatic flight algorithm enables stable and efficient exploration. A radiofrequency modem and long-term evolution router connect the airship to ground control even when it is not in the line of sight. Magnetic data and airship location are monitored in real time and verified using a helicopter. The airship showed high efficiency.